Analisis Independent Study dalam Meningkatkan Kemampuan Bahasa Inggris Mahasiswa Non-English Department - Misnadin dan Sriyono (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2012)
This article highlights the very concern of the English in term of the analysis of Independent Study in improving English proficiency of students of non-English Department. The aspects to be explored covering of activities conducted by the students toward the independent study and the proficiency of the students through independent study. The research using the quantitaive design and the instrumentsused in collecting the data were questionnaires and tests. The data analysis covered preparation, tabulation, and data implementation. The findings showed that activities of independent study conducted by non-English department students were reading English newspapers and magazines, listening and following English programmes in radio, video, etc., and benefitting language laboratory, library, and self access centre and the English proficiency showed significant improvement.